Otimização do processo de soldagem por resistência elétrica em compósitos PEI/fibras contínuas para aplicações aeronáuticas - Abrahão, Ana Beatriz Ramos Moreira [UNESP] (2015)
Thermoplastic composites reinforced with continuous fibers are being studied in a wide range of applications, such as commercial use for their low cost and for engineering with higher associated value. Currently, available polymer matrices for advanced composites have been progressively developed as an alternative for the aeronautical industry and, in the latest years, several special and high performance thermoplastic matrices have been studied for their use in manufacturing advanced composites. Among the thermoplastic matrixes, the poly (ether imide) (PEI) should be highlighted due mainly to its low cost, good mechanical properties, and for being easy to be handled. Moreover, a major problem concerning the use of thermoplastic polymer composites for structural applications is their effectiveness in the integration of structural components. Among the methods available for welding these composites is the use of the electrical resistance welding process which has been considered as the most promising for joining composites. The present work aims to optimize the welding process using electrical resistance matrix composites, consisting of thermoplastic polymer PEI reinforced by glass fiber, carbon fiber and a hybrid system consisting of carbon fiber and glass fiber for aeronautical applications. For the development this work, an experimental design was carried out to determine optimal parameters of time, electrical current and pressure on the welding of the laminates used in this study. Also it was evaluate 4 types of resistive elements (metal mesh stainless steel 100, 200 and 300 mesh, and carbon fiber with bronze). The best optimization parameters were confirmed from the Lap Shear tests. From the main results of these optimization, it was concluded that, for PEI / glass fiber laminates, the best acquired experimental values of current, ... (Complete abstract click electronic access below)